![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
![](https://blog.hocmai.vn/wp-content/uploads/2017/07/hot.gif)
1, Cho [tex]\frac{x}{y} = \frac{y}{z} = \frac{z}{x}[/tex]. So sánh x,y,z ( x + y + z [tex]\neq 0[/tex] )
2, Cho [tex]\frac{a}{b} = \frac{b}{c} = \frac{c}{a}[/tex] và a + b + c [tex]\neq 0[/tex]. Tính [tex]\frac{a^{3}b^{2}c^{1930}}{a^{1935}}[/tex]
3, Cho [tex]\frac{a}{b} = \frac{c}{d}[/tex], chứng minh
a, [tex]\frac{7a^{2}+3ab}{11a^{2}-8b^{2}}[/tex] = [tex]\frac{7c^{2}+3cd}{11c^{2}-8d^{2}}[/tex]
b, ( a + 2c )(b + d) = ( a + c)(b + 2d)
4, CMR
a, Nếu có [tex]\frac{a + 2}{a - 2}[/tex]= [tex]\frac{b + 3}{b - 3}[/tex] thì [tex]\frac{a}{2} = \frac{b}{3}[/tex]
b, Nếu có ac = [tex]b^{2}[/tex] thì a([tex]b^{2} + c^{2}[/tex]) = [tex]c(a^{2} + b^{2})[/tex]
c, Nếu có [tex]\frac{a - c}{c - b} = \frac{a}{b}[/tex] thì [tex]\frac{1}{c} = \frac{1}{2}(\frac{1}{a}+\frac{1}{b})[/tex]
d, Nếu có [tex]\frac{a}{b} = \frac{b}{c}[/tex] thì [tex]\frac{a}{c} = \frac{a^{2}+c^{2}}{b^{2}+c^{2}}[/tex]
e, Nếu có [tex]\frac{a}{b} = \frac{c}{d}[/tex] thì [tex]\frac{2a^{1995}+5b^{1995}}{2c^{1995}+5d^{1995}}[/tex] = [tex]\frac{( a +b)^{1995}}{(c + d)^{1995}}[/tex]
2, Cho [tex]\frac{a}{b} = \frac{b}{c} = \frac{c}{a}[/tex] và a + b + c [tex]\neq 0[/tex]. Tính [tex]\frac{a^{3}b^{2}c^{1930}}{a^{1935}}[/tex]
3, Cho [tex]\frac{a}{b} = \frac{c}{d}[/tex], chứng minh
a, [tex]\frac{7a^{2}+3ab}{11a^{2}-8b^{2}}[/tex] = [tex]\frac{7c^{2}+3cd}{11c^{2}-8d^{2}}[/tex]
b, ( a + 2c )(b + d) = ( a + c)(b + 2d)
4, CMR
a, Nếu có [tex]\frac{a + 2}{a - 2}[/tex]= [tex]\frac{b + 3}{b - 3}[/tex] thì [tex]\frac{a}{2} = \frac{b}{3}[/tex]
b, Nếu có ac = [tex]b^{2}[/tex] thì a([tex]b^{2} + c^{2}[/tex]) = [tex]c(a^{2} + b^{2})[/tex]
c, Nếu có [tex]\frac{a - c}{c - b} = \frac{a}{b}[/tex] thì [tex]\frac{1}{c} = \frac{1}{2}(\frac{1}{a}+\frac{1}{b})[/tex]
d, Nếu có [tex]\frac{a}{b} = \frac{b}{c}[/tex] thì [tex]\frac{a}{c} = \frac{a^{2}+c^{2}}{b^{2}+c^{2}}[/tex]
e, Nếu có [tex]\frac{a}{b} = \frac{c}{d}[/tex] thì [tex]\frac{2a^{1995}+5b^{1995}}{2c^{1995}+5d^{1995}}[/tex] = [tex]\frac{( a +b)^{1995}}{(c + d)^{1995}}[/tex]